Hyalinization of dental pulp tissue due to occlusal trauma (Experimental study (Mustansiria Dental Journal, 2018)
Dental pulp tissue is a highly specialized conneclive tissue contains a formativeand protective cells that can be affected easily by stimuli such as occlusal traumasubjected by occlusal overhang filling.Sixteen albino rats aged range (6-8 months) weight range (0.5-0.75 kg) weresubjected the occlusal overhang filling made for upper first molar for 2 periods, andaccording the periods, rats divided in the 2 groups. Groups I (8rats) subjected forocclusal trauma for 2 weeks duration group II (8rats) subjected for occlusal trauma for8 weeks duration. Histological evaluation have been done for 2.8 weeks usinghematoxyline and eosin stain.Occlusal trauma for 2 weeks in group I showed wide irregular predentin formationwill displacement in odontoblast cell.While in group II for 8 weeks duration, histological feature for pulp tissue showedhyalinization (50-95 μm) in length.Occlusal trauma for long period cause hyalinization of pulp tissue that negativelyinfluence on endodontic treatment in future.